The effect of combined preconditioning strategies on isokinetic strength in well trained kickboxers - Gulsen, M.; Gurses, V.V.; Yilmaz, A. (Sergii Iermakov, 2018)
Background & Study Aim: The use of preconditioning strategies (PconSt) alone has a positive impact on performance. However, it is thought that there will be more impact on the performance of the combined preconditioning strategies, and this is the first work to prove it. This study was to examine the effect of combined preconditioning strategies on isokinetic strength in well-trained kickboxers. Material & Methods: The following preconditioning strategies were combined: morning resistance exercise (MRE), ischemic preconditioning (IP), active warm-up (AW-U), hormonal preconditioning (HP) and post-activation potentiation (PAP). Fifteen well-trained male kickboxers (age: 22.38 ± 4.01years, height: 182.23 ± 1.05cm, body mass: 77.67 ± 8.01kg) volunteered for this study. Peak isokinetic knee extension and flexion moment were determined at 60°/s, 180°/s and 240°/s bilaterally. All participants performed the pre-test and then were randomly divided into Sham and PconSt groups on separate days. For the PconSt group, MRE, IP, AW-U, HP and PAP were implemented sequentially before test. Results: The findings indicated significant increase in strength after combined training in the PconSt groups for right leg flexion at 180°/s flexion (p < 0.05). The average percentage strength difference between sham and PconSt groups was 4.12 ± 8.95%. Conclusionː This study showed that a combined preconditioning strategy increased isokinetic strength.
Keywords: potentiation; LC8-6691; preconditioning; ischemic; post-activation; isokinetic; Special aspects of education; hormonal